PROGRAM LINIER FUZZY PENUH DENGAN METODE KUMAR - Wahyudy, Shintia Devi; Irawanto, Bambang (MATEMATIKA, 2014)
Fully fuzzy linear programing is part of a crisp linear programming (linear programimg with a number of crisp) which the numbers used are fuzzy numbers. Solving a fully fuzzy linear programming problems by using Kumar method to fuzzy optimal solution and crisp optimal value.. Solving fuzzy optimal solution by Kumar method on triangular fuzzy number to divide into tree objective functions and defuzzification by using ranking function and α - cutting to get crisp optimal solution. This paper discusses about Kumar methods method for solving fully fuzzy linear programming in which fuzzy numbers used are triangular fuzzy numbers.